Towards common eating habits in children and teenagers - Manuel Felipe Reig García-Galbis; María Mercedes Rizo Baeza; N. Alarcón; Ernesto Cortes Castell (Universidad de Alicante, 2012)
A study was made about the eating habits of 104 children (12 and 18 years old), in different primary and secondary schools in the urban area of Alicante and the rural area of Murcia. The study took place during the months of March, April and May, taking into consideration there was not exam periods. None of the children studied suffered from an illness which may had influenced their eating habits. For the purpose of the study a weekly survey in which the children wrote their daily food intake was used. Only the surveys with full data were included in the study. Low intake of fish, fruits and vegetables among the subjects was detected. It was also remarkable the low intake of carbohydrates, an increase in the intake of proteins and a decrease in the energy intake recommendable for their age. A change in the eating habits was common for both of the studied groups (rural and urban), becoming equal as an effect of cultural homogeneity, whose extends involves children and teenagers. Despite the fact that weekly surveys are not useful for evaluating the exact quantity of food intake, such as added fat, its use is recommended for detecting deviations more accurately rather than 24 hour surveys.